Vitamin E Supplementation to Quail (Coturnix-coturnix Japonica) Treated by Heat Stress: Effects on Blood Hematology Parameters - Astuti, Farida Kusuma; Rinanti, Rosyida Fajri; Nurul, Mohamad; Tribudi, Yuli Arif (Faculty of Animal Science, Universitas Brawijaya, 2024)
Heat stress is a major problem in poultry farming. Environmental temperature and humidity greatly in fluence the performance of poultry, especially quails raised in tropical environments. Vitamin E is a fat-soluble vitamin that has an antioxidant effect. This study aimed to evaluate the effect of vitamin E supplementation on the blood profile of quails kept under heat stress. This study used 4 treatments of T0 as Control (Commercial Feed + Heat Stress 35 oC); T1 (Control + 100 mg of vitamin E/kg); T2 (Control + 150 mg of vitamin E/kg) and T3 (Control + 200 mg of vitamin E/kg). Observed parameters of leukocytes, heterophylls, lymphocytes and monocytes. The data was analyzed by Analysis of Variant (ANOVA) if there were differences between treatments, followed by the Duncan test. The observation results showed that the addition of vitamin E could increase the number of leukocytes, lymphocytes, monocytes and reduce the number of heterophytes and the H/L ratio of quail blood that experienced heat stroke. Based on the blood profile, the addition of vitamin E as much as 200 mg/kg in feed is able to reduce heat stress due to heat stress in laying quails.